The impact of walking on creative thinking: A systematic review and meta-analysis - Alex Thabane; Vikram Arora; Joelle Boilard; Adam Sutoski; Sameer Parpia; Goran Calic; Jason W. Busse; Tyler McKechnie; Phillip Staibano; Mark Phillips; Roni Reiter-Palmon; Mohit Bhandari (PLoS ONE, 2026)
Background Walking is associated with many benefits, from improved mental health to a reduced risk of mortality – but can it boost creative thinking? Current evidence suggests a positive effect of physical activity on creative thinking, but the specific effect of walking has not been adequately explored. Methods We conducted a systematic search of the PsycINFO, MEDLINE, Scopus, and ProQuest databases from inception to 8 January 2025 using search terms related to walking and creativity. We then performed meta-analyses of Cohen’s d effect sizes to assess the effect of walking on creative thinking, as represented by divergent thinking (the ability to generate novel and useful ideas) and convergent thinking (the ability to analyze and select ideas to find the best solution). We assessed study quality using a creativity-specific tool, and the certainty of the evidence with the Grading of Recommendations Assessment, Development and Evaluation Framework. Results We identified 23 studies (12 randomized experimental studies, nine non-randomized experimental studies, two observational studies) from 16 articles including a total of 1,036 participants, most of whom were post-secondary students. We found moderate certainty evidence of a large effect of walking on divergent thinking ( d = 0.93 [95% CI 0.44, 1.42]), and very uncertain evidence of a null effect of walking on convergent thinking ( d = 0.16 [95% CI −0.31, 0.63]). Sensitivity analyses of randomized trials only found similarly large effects of walking on divergent thinking ability ( d = 0.82 [95% CI 0.35, 1.28]). Conclusion Results suggest that walking likely results in a large increase in divergent thinking, indicating its potential as an intervention to stimulate creative idea generation.